PENGARUH DISIPLIN DAN PRESTASI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. SETIA KAWAN ABADI TULUNGAGUNG - Siawira, Desi Litasari; Nawawi, A. Hasyim; Zainuri, Achmad; Syafrizal, Syafrizal (Commodities, Journal of Economic and Business, 2023)
This study aims to determine and analyze the influence of discipline and work performance on employee productivity at PT. Setia Kawan Abadi Tulungagung. The data of this study were obtained from questionnaires consisting of 5 questions for discipline variables, 6 questions for work performance variables and 7 questions for work productivity variables, literature study, interviews and documentation in accordance with research objectives. Data obtained using the help of SPSS 16.0 (Statistical Product and Service Solutions). The number of respondents is 73 employees of PT Setia Kawan Abadi Tulungagung. Analytical techniques in this study using the validity test, reliability test, multiple linear regression to test the effect of discipline and work performance on employee productivity. The result of the research shows that the regression equation is as follows: Y = 0,492 + 0,495 X1 + 0,794 X2. In F test found F count equal to 369,955 with sig. 0.000 which means discipline and job performance simultaneously have a significant effect on employee work productivity. While from result of t test analysis show value t count of discipline (X1) is 9,948 and work performance (X2) is 18,506 with sig value. = 0.000 because sig value <0,05 hence can be said variable of discipline and work performance have positive effect to work productivity of employees at PT. Setia Kawan Abadi Tulungagung.